A simple synthesis of ZnO:Co2O3 nanocomposites by pulsed laser irradiation in liquid - Kanakkillam, Sreed Sharma; Krishnan, Bindu; Avellaneda Avellaneda, David; Shaji, Sadasivan (2020)
Nanocomposite materials are emerging in popularity due to their enhanced performance over the constituent materials. In this work, we report the fabrication of zinc oxide: cobalt oxide nanocomposites in a simple, fast and room temperature synthesis with good productivity. The nanocomposites synthesized were characterized by SEM, XPS and UV–Visible spectroscopy to analyze their morphology, composition, chemical states, optical absorption, band gap etc. The nanocolloids of the composite were drop casted to form thin films for photocatalytic studies. In SEM analysis, the morphological transformation of the material is observed where it transformed from agglomerated spherical particles to petals shaped and then to partially spherical forms due to pulsed laser irradiation. XPS analysis showed a gradual change in oxygen high resolution spectra in the samples with respect to the concentration difference of cobalt oxide. The optical studies show an enhanced absorption in visible region for the nanocomposite and the energy band gap reduced to 2.4 eV. All the thin films of nanocomposite showed photocatalytic decay of methylene blue dye under visible light irradiation. The results of this study support the effective use of laser irradiation in liquid to obtain